Effect of Chemical Fertilizer and Spraying With Nano Fertilizer In the vegetative and rooting characteristics of cauliflower Brassica Oleracea Var botrytis - Abdul Rahman, Lubna Sabah; Angel, Sabeeh Abdul Wahab; Badr, Basim Rahim (Journal of agricultural, environmental and veterinary sciences, 2018)
The field experiment was conducted during the autumn planting season 2017-2018 In the Research Department of Horticulture and Garden Engineering - Faculty of Agriculture، University of Diyala The experience included 12 Treatment resulting from combinations among the four levels of chemical fertilizer are 0(Without adding fertilizer)، and add 1/3 of the recommended quantity and Add 2/3 of the recommended quantity and 1 add the recommended amount of chemical It has its symbol (T0، T1، T2، T3) Respectively And three levels of nano fertilizer(nano zinc oxide) Research aims To determine the best level of chemical fertilizer and nano fertilizer And determine the optimum level for them to improve the growth of cauliflower، The results showed that the addition of chemical fertilizers in there commended quantity led to a significant increase in plant height 85.93 cm and number of leaves 23.09 leaf plant and leaf area 252.64 plant fat Root length is 23.55 cm and root diameter is 7.05 mm The results also showed that spraying the nano fertilizer of 50 mg per liter-1led to a significant Plant height 82.79 cm and number of leaves 22.09 leaf plant and leaf area 251.30 plant fat root length 21.33 cm and root diameter 5.95 mm.
Keywords: cauliflower; chemical fertilizer; nano fertilizer